Performance index analysis of various 3.5KVa/48V power inverters - Godspower Onyekachukwu Ekwueme; Ifeyinwa Faith Ogbodo (Science: Indonesian Journal of Science, 2025)
The initial cost of the power inverter system is significantly higher compared to the conventional source of power. As a result, there is needed for the performance evaluation of various power inverters in order to determine the cost efficiency of the power inverter as an alternative source of power. The aim of the present study is to investigate the performance index of 3.5kva/48v inverters for a domestic source of electric power supply. Four types of inverters (mercury and safer power, sinergy and su-kam) commonly available in the market were considered. And three performance indices (resistive load test, inductive load test and output waveform) were used to determine the cost effectiveness of one inverter over the other. Results showed that the sinergy power inverter has the best performance. In terms of the battery discharge current, sinergy is 35% (for the resistive) and 61% (for inductive test) more efficient compared to mercury at an output load of 1 kw.